Increased disease calls for a cost-benefits review of marine reserves. - Emma C Wootton; Andrew P Woolmer; Claire L Vogan; Edward C Pope; Kristina M Hamilton; Andrew F Rowley (PLoS ONE, 2012)
Marine reserves (or No-Take Zones) are implemented to protect species and habitats, with the aim of restoring a balanced ecosystem. Although the benefits of marine reserves are commonly monitored, there is a lack of insight into the potential detriments of such highly protected waters. High population densities attained within reserves may induce negative impacts such as unfavourable trophic cascades and disease outbreaks. Hence, we investigated the health of lobster populations in the UK's Marine Conservation Zone (MCZ) at Lundy Island. Comparisons were made between the fished, Refuge Zone (RZ) and the un-fished, No-Take Zone (NTZ; marine reserve). We show ostensibly positive effects such as increased lobster abundance and size within the NTZ; however, we also demonstrate apparent negative effects such as increased injury and shell disease. Our findings suggest that robust cost-benefit analyses of marine reserves could improve marine reserve efficacy and subsequent management strategies.